PERAN IMPLEMENTASI GREEN BANKING PADA BANK SYARIAH INDONESIA - Lelawati, Nina; Darmayanti, Elmira Febri; Nusantoro, Jawoto (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2023)
Banking that prioritizes social and environmental finance and the preservation of natural resources is known as "green banking". Man has an obligation to take care of the environment he has created through the preservation of the environment. The objectives of this study are: (1) Knowing the green banking program implemented by Bank Syariah Indonesia, and (2) knowing that the green banking program is implemented at Bank Syariah Indonesia. Qualitative proximity and descriptive analysis become research models through literature study activities of similar research. The secondary data used came from the findings of other researchers. Thecomponents of data analysis activities are as follows: 1) reducing data, 2) presenting data, and 3) drawing conclusions. According to research findings, Islamic banking in Indonesia has adopted environmentally friendly practices such as the efficiency of paper and electricity use, water use efficiency, waste management and reduction, and the efficiency of paper use and use. The tauhid value of the Islamic economic system is upheld by Bank Syariah Indonesia's green banking model which is very similar to the green banking business model.